Carbon and Biomass Density of Trees in Duggada Area of Garhwal Himalaya, India - Iqbal, Kaiser; Bhat, Jahangeer A.; Pala, Nazir A.; Hussain, Aatif; Negi, Ajeet K. (Indian Forester, 2014)
Forests often store carbon at rates well below their potential and thus could be responsive to the management of enhanced carbon sequestration. The present study was carried out in Duggada area of Garhwal Himalaya to assess tree biomass and total carbon density. The dominant tree species were found Salix tetraseprma, Toona hexandra, Emblica -1 officinalis and Acacia catechu. Total carbon density was 525.15 mg ha and ranged between 81.27±4.82 for Bischofia -1 -1 javanica to 4.38±0.29 mg ha for Ficus religosa. Total tree biomass density (TBD) was 1050.30 mg ha and values varied -1 from 162.54±9.65 in Bischofia javanicato 8.77±0.59 mg ha for Ficus religosa. However, value of below ground biomass density (BGBD) was 806.95 and range between 128.8±7.85 for Bischofia javanicato 6.41±0.45 in Ficus religosa.